The Influence Of Motivation And Social Support On The Decision To Work Abroad - Puspita, Happy; Habiburrahman; Haninun (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2026)
This study aims to analyze the influence of motivation and social support on the decision to work abroad among Generation Z in Pasir Sakti District, East Lampung Regency. The increasing number of Generation Z choosing to work abroad indicates the presence of internal and external factors that affect work decision-making. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 115 Generation Z respondents currently working abroad. The data analysis techniques used include descriptive statistical analysis and multiple linear regression analysis, with hypothesis testing through t-tests, F-tests, and the coefficient of determination. The results of the study show that motivation has a positive and significant effect on the decision to work abroad. Social support is also proven to have a positive and significant effect on the decision to work abroad. Simultaneously, motivation and social support have a significant effect on Generation Z's decision to work abroad, with motivation being the most dominant variable. These findings indicate that the decision to work abroad is influenced not only by economic factors but also by internal drives and social environmental support. This research provides important implications for local governments and relevant stakeholders in designing accompaniment policies and strengthening human resources so that labor migration is carried out consciously, safely, and sustainably.